The efficacy and safety of niacin on hyperphosphatemia in ESRD patients undergoing hemodialysis: randomized controlled trial - Hanan Mahmoud Ahmed; Esraa Yossif; Alaa S. Abd-Elkader; Essam M. Abdel Aziz (SpringerOpen, 2022)
Abstract Background Hyperphosphatemia is a common complication of end-stage renal disease (ESRD) and particularly affects hemodialysis (HD) patients. Elevated serum phosphorus contributes to the development of secondary hyperparathyroidism, chronic kidney disease-mineral bone disorder (CKD-MBD), metastatic calcifications and calcific uremic arteriolopathy. There is a significant association between hyperphosphatemia and increased morbidity and mortality in ESRD patients including cardiovascular morbidity and mortality, and it is also associated with prolonged hospitalization of HD patients. This study aim to evaluate the serum phosphorus lowering effect of niacin in HD patients. Results There was a decrease in phosphate values during the first 3 months of the study in the niacin group, with a significant change in phosphate level at the third month (5.90 ± 0.52 vs. 6.42 ± 0.65 (mEq/l); P <  0.001) and at the sixth month (5.12 ± 0.41 vs. 5.76 ± 0.47 (mEq/l); P <  0.001) compared to the control group. It was noted that both groups had an insignificant difference regarding baseline parathormone (PTH), though the PTH showed a significantly lower level at the third month (192.39 ± 78.85 vs. 388.27 ± 263.10 pg/ml; P <  0.001) and at the sixth month (127.56 ± 90.87 vs. 249.85 ± 97.69 pg/ml; P <  0.001) in the niacin group. Conclusion Niacin caused a statistically significant decrease in levels of phosphate and PTH in dialysis patients. Trial registration Registered at ClinicalTrials.gov NCT03163576 . Trial registration date: 22 May 2017. Date of first patient's enrolment: 1 October 2018. Date of the ethical committee approval: 29 March 2017. Number of the ethical committee approval: 17100040.